Fibro-osseous lesions of the paranasal sinuses and the skull base - Alturaiki, Sajedh M.; Almomen, Ali; Al Azzeh, Ghaleb; Al Khatib, Abdulrahman; Alshaikh, Nada (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Osteomas, ossifying fibromas, and fibrous dysplasia comprise a set of benign neoplasms known as fibro-osseous lesions (FO), which can arise in the paranasal sinuses. The vast majority of benign FO lesions (BFOL) are incidental findings on radiographs. They tend to be slow-growing tumors, and are infrequently symptomatic. The management strategy can vary significantly for theses lesions. This can range from serial, observations to aggressive surgical resection, based on symptomatology, size, and location of the lesion. Methods: Retrospective analysis of all the data of different symptomatic FO of the paranasal sinuses and the skull base was performed at King Fahad specialist hospital, Dammam, KSA (2006 to 2017). Results: A total of 21 patients were identified; 10 (46.7%) patients were diagnosed with osteoma, 8 (38.1%) with ﬁbrous dysplasia, 2 (9.5%) with ossifying fibroma and one (4.8%) with juvenile active ossifying (JAOF), 17 were adults and 4 were children, the range of f/u (3-60) months. 19 patients were managed by the endonasal endoscopic approach. They continue to be followed with no evidence of recurrence. Two cases required the revision combined endoscopic open approach to ensure adequate removal of the disease (residual and recurrence). Conclusions: Diagnostic dilemma of BFOL can be overcome with a combination of clinical, radiological and pathological criteria. Correct diagnosis of fibro-osseous tumors is crucial for adequate therapy as their treatment, prognosis, clinical aggressiveness and long term complications of individual entities vary significantly. Endoscopic computer-assisted surgery is the treatment of choice. Endoscopic resection remains a technical challenge.